Sex differences in ketogenic diet: are men more likely than women to lose weight? - Jiao, Yingying; Chen, Xiuru; Liu, Lu; Lu, Yantong; Gao, Minghuang; Wang, Qi; Chi, Xiaoling; Mo, Yousheng (Frontiers in Nutrition, 2025)
As economy is growing, the number of patients living with obesity has rapidly increased globally. Patients with obesity or diabetes have become a serious global health issue that requires the attention and participation of society as a whole. The ketogenic diet, as an emerging nutritional therapy for improving obesity, takes into consideration the differences between sexes in genetic variation, hormonal balance, and body fat distribution. The aim is to elucidate the effectiveness of sex differences in ketogenic dieting for weight loss and to explore suitable weight loss strategies. In this review, we delve into the physiological sexual differences between men and women in terms of fat and muscle tissue and discuss the sex-specific potential mechanisms underlying the differential effects of the ketogenic diet for weight loss. Based on this foundation, we further propose brief weight loss recommendations beneficial for both men and women. It is hoped that, in this direction, the optimization of short-term or long-term clinical weight loss programs can be developed based on sexes.